An Update on the Use of Massive Transfusion Protocols in Obstetrics. Issue 1 (March 2017) - Pacheco, Luis D.; Saade, George R.; Costantine, Maged M.; Clark, Steven L.; Hankins, Gary D. V.
Abstract : ( Am J Obstet Gynecol. 2016;214(3):340–344) Peripartum hemorrhage due to increased cesarean deliveries and placental anomalies is a significant cause of maternal mortality worldwide. Alternate pathways have been suggested to play an important role in the pathophysiology of massive hemorrhage. Research evidence suggests that hemostatic resuscitation can improve outcomes compared with traditional resuscitation protocols. Massive transfusion protocols administer blood products early in the resuscitation process and have been adopted widely in the United States for severe hemorrhage treatment. This review aimed to address updates on the use of massive transfusion protocols for obstetrical hemorrhage.